Profiling cannabis consumption motivation and situations as casual leisure - Sophie Ghvanidze; Soo K. Kang; Milan Ščasný; Jon Hanf (Charles University in Prague, Institute of Economic Studies (IES), 2024)
It is a common practice in many cultures to use cannabis as a casual leisure activity, particularly for socialization and entertainment in North America and Europe. This study examines the daily use of cannabis and its connection to entertainment and socialization. The research surveyed young adults in Germany utilizing an online survey and evaluated the Marijuana Motives Measure, which focuses on four motivation factors for using cannabis and how they relate to different situations. The survey included ten comprehensive consumption locations and situations, representing the first study to explore the underlying motivation for cannabis use in adults' daily lives and its relation to individual characteristics and consumption situations. The primary reason for using cannabis is for hedonic pleasure, relaxation, and enhancing social experiences. Male respondents tend to be more motivated by conformity, while millennials and more educated cannabis users prioritize hedonic pleasure, relaxation, and sociable conversation.
Keywords: 330; cannabis consumption; motivation; situations; casual leisure; Marijuana Motives Measure